Sexual Development in Perinatally HIV-Infected Young People: A Systematic Review and Explorative Study. Issue 6 (20th October 2022) - ter Haar, A.M.; Fieten, A.; Van den Hof, M.; Malekzadeh, A.; Laan, E.T.M.; Oostrom, K.J.; Pajkrt, D.
Abstract: Background: Similar to other young people with a chronic health condition, perinatally HIV-infected (PHIV) adolescents may have an impacted sexual development. Objectives: This paper aims to compare sexual milestones of PHIV to HIV uninfected peers, through a systematic review (SR) and explorative study. Methods: We performed a systematic search in 4 electronic databases (Medline, Embase, Web of Science, and Scopus), according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Last search in all databases was performed in May 2021. We included studies that reported on quantitative data of any of the main outcomes and compared PHIV to HIV uninfected control groups. Main outcomes were defined as the occurrence and/or debut age of sexual milestones (falling in love, having been in a romantic relationship, masturbation, kissing, non-genital caressing (feeling or petting, touching), genital caressing (fingering, handjob), giving or receiving oral sex, and penetrative sex (vaginal or anal). We excluded case reports, audits, guidelines, editorials, abstracts, studies that reported on behaviorally infected HIV patients, studies that did not include an HIV uninfected control group and studies that could not be translated to English or Dutch. We used the Agency for Health Care Research and Quality (AHRQ) Checklist for quality assessment. We performed qualitative synthesis of the data. In the explorative study, we compared sexual milestones of PHIV and HIV uninfected controls matched for age, sex, ethnicity and educational level, using a subset of questions of a validated questionnaire. Results: We included eighteen studies in the SR, describing outcomes of an estimated 1, 963 participants. Seventeen studies compared the occurrence and/or debut age of intercourse in PHIV and HIV uninfected controls and 4 studies reported on any of the other sexual milestones. The majority of studies found no difference in occurrence (12 of 16 studies) or debut age (6 of 8 studies) of intercourse in PHIV compared to controls. Two of 4 studies reporting on any of the other milestones found no significant differences between PHIV and HIV uninfected controls. In the explorative study, we included ten PHIV participants and 16 HIV uninfected, matched controls. PHIV tended to report a later debut age of sexual milestones than controls (not significant). Strengths and Limitations: The SR includes only a small number of studies and few studies report on non-penetrative milestones. The explorative study adds to this review by including non-penetrative milestones and comparing PHIV to HIV-uninfected, well-matched controls. However, the sample size was small. Conclusion: PHIV seem to engage in sexual activities and achieve sexual milestones at a similar rate as their HIV uninfected peers, with a tendency of a later start in well treated PHIV. The review was registered in the PROSPERO database (CRD42021252103) and funded by AIDSfonds. AIDSfonds had no role in the study design or interpretations of this study.